THE ROLE OF EDUCATION IN NATIONAL DEVELOPMENT: NIGERIAN EXPERIENCE - E. Orji Kingdom; Job Maekae (European Scientific Journal, ESJ, 2013)
This paper emphasizes the contributions of education to national development. It stresses the fact that a nation develops in relation to its achievement in education. This explains why contemporary world attention has focused on education as an instrument of launching nations into the world of science and technology and with consequential hope of human advancement in terms of living conditions and development of the environment. This is because, education, in the life of a nation, is the live wire of its industries and also the foundation of moral regeneration and revival of its people. It is also the force and bulwark of any nation’s defence and it has been observed that no nation rises above the level of its education. Seeing education in this perspective calls for proper funding from federal, state and local governments to make the sector produce the desired results which will stimulate national development. In Nigeria, much is not being derived from the sector due to neglect on the part of government, corruption, policy discontinuity, inter alia. To make the nation derive maximum dividends from the sector, useful recommendations are made.